KOMPARASI RISIKO PRODUKSI DAN PENDAPATAN USAHATANI KOPI ORGANIK DAN AN ORGANIK: (Suatu Kasus di Desa Margamulya, Kecamatan Pangalengan, Kabupaten Bandung) - Tuti Karyani; R. Az-Zahra S; E. Djuwendah; E. Supriyani R (Jurnal Penelitian Pertanian Terapan, 2022)
Changes in consumer lifestyle have led to an increasing demand of organic products. The government supports the growth of the organic-product trend by establishing 1000 organic-farming village program. The transformation of farming method from the conventional (inorganic) one to the organic one certainly imposes risks that need to be considered. This study aims to analyze the differences of production risks and income risk between organic and inorganic coffee farmers. The research was conducted in Margamulya Village, Pangalengan District, West Java, which was purposively chosen because Margamulya Village is the center of coffee production in West Java and is one of the villages selected in the 1000 organic-farming-village program. The samples used in this study amounted to 56 respondents, which consisted of 28 organic farmers and 28 conventional farmers that were obtained through Slovin’s formula and selected by simple random method. The method used in this research was comparative quantitative research method. The data were analyzed using comparative analysis by coefficient comparison analysis of production risks and income risks. The results show that the production risks and income risks of inorganic coffee farmers are higher than those of organic farmers. Keywords: Organic Coffee, Production Risks, Income Risks